Proton Pump Inhibitors and Gastric Cancer - Seungkyung Kang; Soo-Jeong Cho (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Concerns have been raised regarding the long-term use of proton pump inhibitors (PPIs) as an important risk factor for gastric cancer in clinical practice. PPIs can cause hypergastrinemia at clinical doses, and hypergastrinemia has been reported to induce malignant neoplasms in the stomach in previous animal studies. In humans, the proliferation of enterochromaffin-like (ECL) cells induced by hypergastrinemia is suspected as a potential mechanism of gastric cancer. Meanwhile, persistent Helicobacter pylori (H. pylori) infection causes gastric atrophic change, which itself is a major cause of gastric cancer, and it can further increase the risk of gastric cancer by strengthening corpus atrophy through interaction with PPIs. Recent epidemiologic studies have reported an important link between long-term PPI intake and gastric cancer risk even after successful eradication of H. pylori. However, due to the methodological limitations of observational clinical studies, the causal relationship is still not clear, and a recent big data-based study reported that long-term PPI use was not related to gastric cancer incidence. Taken together, despite the potential detrimental effects of PPIs, it is currently difficult to draw a definite conclusion about its association with gastric cancer. To minimize the possibility of gastric cancer in H. pylori-infected patients or precancerous lesions in long-term PPI users, long-term PPI administration should be limited to the minimum effective dose, and antibacterial treatment for H. pylori should be considered.